Lumberjanes: unicorn power! - Tamaki, Mariko (Lumberjanes, 2017)
"Welcome to Miss Qiunzella Thiskwin Penniquiqul Thistle Crumpet's Camp for Hardcore Lady Types. The five scouts of Roanoke cabin--Jo, April, Molly, Mal, and Ripley--love their summers at camp. They get to hang out with their best friends, earn Lumberjane scout badges, annoy their no-nonsense counselor Jen. and go on supernatural adventures. That last one? A pretty normal occurrence at Miss Qiunzella's, where the woods contain endless mysteries. Today is no exception. When challenge-loving April leads the girls on a hike up the TALLEST mountain they've ever seen, things don't go quite as planned. For one, they didn't expect to trespass into the lands of the ancient Cloud People, and did anyone happen to read those ominous signs some unknown person posted at the bottom of the mountain? Also, unicorns"--